The principles of the Taoist view of life - فارس, سەرتیپ عەزیز (Sulaimani Journal for Humanities, 2019)
Taoism is a compilation of Chines concepts that mold the Chines notion a long time ago and had its own vision to live beside Confucianism, Taoism has been attributed to Lau Tzu the philosopher or the Old Tutor who was motivated by problems of his society like wars, unethical competition and social corruption to put his ideas in a small book but deep in meaning called (Tao Te Ching). Taoism has been developed to form two main tendencies, philosophical Taoism and Ritual or Religious Taoism. Taoism is an attempt to organize the society according to Lau Tzu and to resemble the Taoism Ideals which is Tao. This research considerate the origins of Taoism concept to life, in which the Taoist can leave greed competition, showmanship and attaching to life, in a way that an individual can do his job without any social or legal pressures and without expecting any rewards from society or authorities. Simplicity is a Taoist characteristic and life according to him\ her is relativity between positive and negative forces or what is called (Yin and Yang)